Micropropagation of Mangosteen (Garcinia Mangostana L.) by Direct and Indirect Organogenesis - Suci Rahayu, (2007)
The mangosteen (Garcinia mangostana L.) still remains an under exploited tropical fruit species that has potential to be developed for local consumption and export commodity. The problem for large scale planting of this plant is not having enough planting materials because the conventional vegetative propagation method has low percentage of success. One of the alternative approaches for mass propagation of mangosteen is through tissue culture. The advantages of propagation through tissue culture are mass propagation can be achieved in a short of time period, plantlet can be produced all year round, and require less space of the plant in the laboratory compare with to the field. The result of the study on in vitro propagation of mangosteen in terms of production of adventitious shoots through direct organogenesis and indirect organogenesis in term of callus induction was conducted at the laboratory of Faculty of Agriculture, Universiti Putra Malaysia. It was observed that among 24 initiation media tested, 16 mg/l BAP gave the highest number of shoots (7.00 shoot/explant), followed by 8 mg/l BAP (6.3 shoots/explant) after eighth weeks of culture. In general, the supplement of AdS in media did not significantly influence the number of shoots produced. There was negative correlation between the height of shoot and the number of shoot produced. The highest number of shoots was recorded on media with 1 mg/l and 2 mg/l BAP, while the shortest shoot was on media of 16 mg/l and 8 mg/l BAP. Contrary to the height of shoot, there was positive correlation between the weight of shoots and the number of shoots. Treatment with 16 mg/l and 8 mg/l BAP gave the highest weight of shoots produced per seed explant. During subculture, treatment with BAP 2 mg/l gave the highest number of shoots at every occasion of subculture (39.56 shoots per explant), followed by 1 mg/l BAP (27.71 shoots per explant). Height of shoots on all media of subculture did not significantly differ. Combination of 1 mg/l BAP and 2 mg/l Kinetin was the most suitable media for elongation of the shoot (1.06 cm). Among the rooting media, ½ MS + 15 mg/l NAA + 0.05% Charcoal + 10 g/l sucrose was most suitable for the emergence of roots with 3.4 roots per shoot). While ½ MS + 1 mg/l IAA + 0.05% Charcoal + 10 mg/l sucrose seemed to be most suitable media for lengthening the roots. The average length of root on this media was 6.85 cm per shoot. Plantlets from rooting experiments acclimatized on the media of soil + sand + peat (2 : 1: 1) have grown well. 100% of them could survive under misting chamber condition for eight weeks. In study on organogenesis through callus induction, all media with the exception of MS, BAP alone and 2,4-D alone could produce calli. It is expected that this findings can contribute to the knowledge of science, particularly on in vitro propagation of mangosteen, and can be used as a reference for other students and researchers as well as agricultural industries in developing mass propagation of mangosteen.